The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1111/j.1528-1157.1984.tb03488.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Distribution of Carbonic Anhydrase and Na+,K+‐ and HCO3‐‐ATPases in Brains of DBA and C57 Mice

Abstract: DBA/2J mice are susceptible to audiogenic seizures (ASs) in an age-dependent manner, susceptibility being maximal at 21 days of age and declining thereafter. DBA, as compared with AS-resistant C57BL/6J (C57) mice, had higher carbonic anhydrase (CA) activity in cerebral cortex, brainstem, and cerebellum homogenates at 21 days of age. CA activity was also increased in cytosolic (82%), microsomal (167%), and myelin (68%) subcellular fractions from cerebral cortex, and in cytosolic (51%) and mitochondrial (102%) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
3
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
3
3
0
Order By: Relevance
“…In all three tissues examined there was a significant increase in CA activity in DBA control mice as compared with C57 control mice. This observation is in agreement with those previously reported (Engstrom et al, 1984b). In CC, CB, and BS, there was a significant decrease in CA activity in chronically treated as compared with control DBA mice.…”
Section: Chronic Actz Administration: Effect On Actz Eds0 Valuessupporting
confidence: 95%
See 2 more Smart Citations
“…In all three tissues examined there was a significant increase in CA activity in DBA control mice as compared with C57 control mice. This observation is in agreement with those previously reported (Engstrom et al, 1984b). In CC, CB, and BS, there was a significant decrease in CA activity in chronically treated as compared with control DBA mice.…”
Section: Chronic Actz Administration: Effect On Actz Eds0 Valuessupporting
confidence: 95%
“…Cerebral cortex (CC), cerebellum (CB), and brainstem (BS) tissues were collected, cleared of meningeal tissue, and homogenized. CA activity and protein content were determined on these homogenates according to the methods of Maren (1960) and Lowry et al (1951), respectively, as previously described by Engstrom et al (1984b). CA activity and protein content were also determined on brain tissues obtained from mice of the same age of both strains that had received no ACTZ.…”
Section: Chronic Actz Administration: Effect On Ca Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Uptake of 36Cl-, 22Na+, and '"Iby astrocytes (C/M) of DBA, C57, and SW mice can either enhanced or inhibited by drugs acting on specific transport systems (Table 3). It is apparent that responses of these cultured astrocytes to drugs commonly used in transport studies are very similar to those in brain and other tissues reported previously (Chow et al, 1983~1, 1987(Chow et al, 1983~1, , 1990Engstrom et al, 19846;Woodbury et al, 1984).…”
Section: Discussionsupporting
confidence: 81%
“…26, NO. l , 1985 thermore, Engstrom et al (1983) have recently demonstrated that in audiogenic seizure-susceptible DBA mice, carbonic anhydrase activity in cerebral and cerebellar cortex is highest at postnatal day 21, the period when the animals are maximally susceptible to audiogenic seizures. Thus, it appears that the increased activity of these two enzymes observed in various cerebral tissues of the audiogenicsusceptible mouse are compensatory for increased levels of neuronal activity.…”
Section: Discussionmentioning
confidence: 99%